2022
DOI: 10.1109/tmag.2022.3167246
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Coercivity Enhancement >1T for Nd-Fe-B Permanent Magnets With 20 wt% Nd Produced by Laser Powder Bed Fusion

Abstract: The impact of laser powder bed fusion (LPBF) on coercivity of Nd-lean commercial MQP TM -S powder is investigated. It is found that different processing parameters, such as laser power, scan velocity and hatch spacing, have a remarkable impact on the magnetic performance of LPBF-processed Nd-Fe-B permanent magnets. The increase of energy input during manufacturing will also increase coercivity and a maximum value of 920 kA/m (µ0Hc = 1.15 T) was achieved without any further post-processing. Among other paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[12][13][14][15] PBF-LB of commercial Nd-Fe-B magnet micropowders has already been studied in the literature, mainly focusing on laser processing parameters and their correlation to mechanical or magnetic properties. [16][17][18][19][20][21][22][23][24][25][26][27][28] It has been reported that direct energy deposition [29] or PBF-LB/M [21] of the commercially available Nd-Fe-B micropowder [30] (called MQP-S, see methods section for details) may cause the decrease or even absence of a hard magnetic phase. A recent study conducted by Tosoni et al [23] showed that the high cooling rates utilized in PBF-LB/M are advantageous for functional materials like Nd-Fe-B.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] PBF-LB of commercial Nd-Fe-B magnet micropowders has already been studied in the literature, mainly focusing on laser processing parameters and their correlation to mechanical or magnetic properties. [16][17][18][19][20][21][22][23][24][25][26][27][28] It has been reported that direct energy deposition [29] or PBF-LB/M [21] of the commercially available Nd-Fe-B micropowder [30] (called MQP-S, see methods section for details) may cause the decrease or even absence of a hard magnetic phase. A recent study conducted by Tosoni et al [23] showed that the high cooling rates utilized in PBF-LB/M are advantageous for functional materials like Nd-Fe-B.…”
Section: Introductionmentioning
confidence: 99%